Bond line thickness and die tilt inspection in die bonding process. (18th May 2016) - Chen, Po-Cheng; Chang, Ming; Lai, Wei-Chung; Gabayno, Jacque Lynn
Abstract: This study focuses upon building an automated inspection system for the in-line measurement of bond-line thickness (BLT) and die tilt in die attachments in the semiconductor packaging process. A prototype of a visual system utilizing the line scan stereo vision technique via two linear CCD cameras has been developed for the die bonding quality inspection. A novel algorithm is proposed for the determination of the 3D coordinates of certain points on an object. The BLT and die tilt of a die attached chip of substrate height 800 μm and cross section 15 × 15 mm 2 were measured to be approximately 76.8 μm and 0.00094, respectively. The measurement can be completed within one second. Thus the in-line inspection of die bonding quality can be conducted efficiently using the proposed technique.